Strategi PT. BPR Balerong Bunta dalam Percepatan Konversi ke BPR Syariah - Fitri Yenti; Yani Rahmadanti; Awaluddin Awaluddin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The research aims to find out the strategies carried out by PT BPR Balerong Bunta in the process of accelerating the conversion from conventional banks to Islamic banks. This type of research is field research with a qualitative descriptive approach. Data analysis techniques are carried out through data collection by interview, data reduction, data display and conclusion drawing. The results showed that the strategy carried out by PT. BPR Balerong Bunta in accelerating the conversion was to form a special team named the conversion team, conduct a comparative study, make a conversion business feasibility study, coordinate directly with prospective Sharia Supervisory Board and the board of commissioners, as well as conduct weekly meetings, complete the conversion requirements regulated by the Financial Services Authority, prepare core banking IT, conduct training and development of directors and employees